Legalising land rights : local practices, state responses and tenure security in Africa, Asia and Latin America - Ubink, Janine M., 1976-; Hoekema, A. J.; Assies, Willem (Law, governance, and development. Research., 2009)
An incisive study of local land rights in developmental countries with suggestions for a new approach.